2019
DOI: 10.1175/jcli-d-18-0813.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Seasonality of the El Niño Teleconnection to the Amundsen Sea Region

Abstract: The Amundsen Sea low (ASL) is a quasi-stationary low pressure system that affects climate in West Antarctica. Previous studies have shown that El Niño–Southern Oscillation (ENSO) modulates the position and strength of the ASL with the strongest teleconnection found in austral winter despite the amplitude of ENSO events generally being largest in austral autumn/summer. This study investigates the mechanisms behind the seasonality of the El Niño teleconnection to the Amundsen Sea region (ASR) using experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
5
39
1
Order By: Relevance
“…Furthermore, Turner et al (2016) recently showed that over the 1999-2014 negative IPO period, the Antarctic Peninsula cooled, and Clem et al (2018) showed that the negative IPO warmed the Ross Ice Shelf. However, they note that in austral summer when Antarctic Peninsula cooling is strongest, the tropical teleconnection is weak because of unfavorable conditions for Rossby wave propagation into high latitudes (Jin & Kirtman, 2009;Scott Yiu & Maycock, 2019). Moreover, they are not fully consistent with ASL deepening.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, Turner et al (2016) recently showed that over the 1999-2014 negative IPO period, the Antarctic Peninsula cooled, and Clem et al (2018) showed that the negative IPO warmed the Ross Ice Shelf. However, they note that in austral summer when Antarctic Peninsula cooling is strongest, the tropical teleconnection is weak because of unfavorable conditions for Rossby wave propagation into high latitudes (Jin & Kirtman, 2009;Scott Yiu & Maycock, 2019). Moreover, they are not fully consistent with ASL deepening.…”
Section: Introductionmentioning
confidence: 98%
“…Turner et al () attributed the recent Antarctic Peninsula cooling to increased cyclonic activity in Drake Passage. However, they note that in austral summer when Antarctic Peninsula cooling is strongest, the tropical teleconnection is weak because of unfavorable conditions for Rossby wave propagation into high latitudes (Jin & Kirtman, ; Scott Yiu & Maycock, ). Therefore, while prior studies implicate the IPO as an important driver of West Antarctic decadal climate variability, no consistent explanation links the recent negative IPO event to the reversal in West Antarctic climate trends.…”
Section: Introductionmentioning
confidence: 99%
“…However, Raphael et al (2016) found that the seasonal location of the ASL does not always coincide with the center of maximum storm activity. Several other recent studies (e.g., Yiu & Maycock, 2019, 2020 have linked the existence of the ASL to zonal asymmetries in tropical sea surface temperatures (SSTs) via planetary scale Rossby wave activity from the tropics to the southern high latitudes.…”
mentioning
confidence: 99%
“…RWT result from reduced (enhanced) Walker Cell convection in the tropics in austral winter during El Niño (La Niña) events. This causes the Pacific South American (PSA) pattern of high-low-high (low-high-low) tropospheric pressure anomalies that propagate south-eastward from the equatorial Pacific toward the South Pacific (Yiu and Maycock 2019). Proxy records for the ENSO from tree-ring, coral and ice core records have been used to produce multi-centennial reconstructions of the ENSO (e.g., Braganza et al 2009;Carré et al 2014;Cobb et al 2003;Cobb et al 2013;Dätwyler et al 2019;Emile-Geay et al 2016;Freund et al 2019;Fowler et al 2012;Grothe et al 2019;Stahle et al 1998).…”
Section: Introductionmentioning
confidence: 99%